2023
DOI: 10.1111/jen.13122
|View full text |Cite
|
Sign up to set email alerts
|

The gut bacterium Serratia marcescens mediates detoxification of organophosphate pesticide in Riptortus pedestris by microbial degradation

Abstract: Organophosphate insecticides have been widely used in agriculture to control insect pests and raised growing problems including insecticide resistance. According to recent studies, microbial symbionts play important roles in developing insecticide resistance. The bean bug Riptortus pedestris is a notorious pest of leguminous crops, harbouring diverse microorganisms in their insect midguts. However, the potential biological roles of many gut‐associated bacteria are largely unknown. In this study, we isolated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Most symbionts that mediate the detoxification of pesticides are facultative symbionts [ 7 , 8 , 41 ] that are acquired from the environment. Although previous studies have reported that diverse microorganisms from the environment, including bacteria from the Paracoccus , Pseudomonas , Rhodococcus , and Bacillus genera have the capacity to degrade buprofezin as their sole source of carbon and energy for growth [ 17 , 19 , 42 , 43 ], none of these bacteria were linked to buprofezin-resistance in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most symbionts that mediate the detoxification of pesticides are facultative symbionts [ 7 , 8 , 41 ] that are acquired from the environment. Although previous studies have reported that diverse microorganisms from the environment, including bacteria from the Paracoccus , Pseudomonas , Rhodococcus , and Bacillus genera have the capacity to degrade buprofezin as their sole source of carbon and energy for growth [ 17 , 19 , 42 , 43 ], none of these bacteria were linked to buprofezin-resistance in our study.…”
Section: Discussionmentioning
confidence: 99%
“…pedestris has shown that S . marcescens can utilize the herbicide atrazine and the insecticide dimethoate respectively as the sole carbon resources for growth and enhance host resistance to these compounds [ 6 , 41 ]. In addition, research on buprofezin resistance in the small brown planthopper infected with S .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bean bug, Riptortus pedestris (Hemiptera: Alydidae), is a major agricultural pest that is widely distributed in East Asia, such as South Korea, Japan, and China, resulting in significant yield losses and low seed quality of soybean (Glycine max), which is an important oil and cash crop (Shan et al, 2021;Wei et al, 2023). Evaluation of the associations between bean bugs and gut bacteria was performed in R. pedestris (Jang et al, 2023;Wei et al, 2023;Xia et al, 2023). For example, a specific gut bacterial symbiont, Caballeronia insecticola (Burkholderia insecticola), promoted the proliferation of stem cells and simultaneously inhibited apoptosis at the tip of gut crypts in R. pedestris (Jang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%